Dimensional stability of heat oil-cured particleboard made with oil palm trunk and rubberwood - Lee, Seng Hua; Ashaari, Zaidon; Ang, Aik Fei; Abdul Halip, Juliana (Springer, 2015)
Dimensional stability of heat oil-cured particleboard made with admixture of oil palm trunk and rubberwood was evaluated. Particleboard made with oil palm trunk had better dimensional stability due to better compact ratio and lower hygroscopicity than rubberwood. Combination of repellent properties of oil and application of heat had greatly reduced the hygroscopicity of particleboard by decreasing its equilibrium moisture content, thickness swelling and water absorption.